Membranous glomerulonephritis and tuberculous peritonitis: a rare association - Ghosh, Biswadip; Pande, Arindam; Ghosh, Anirban; Banerjee, Arnab; Saha, Sandip (The Journal of Infection in Developing Countries, 2011)
Membranous glomerulonephritis is rarely associated with tuberculosis infection. We report a case of a 24-year-old female with tuberculous peritonitis associated with membranous glomerulonephritis causing subnephrotic range proteinuria. Histological examination confirmed both diagnoses. The patient showed improvement with anti-tubercular drugs over six months of follow-up.